PERANCANGAN IKLAN LAYANAN MASYARAKAT “SPORT ANYWHERE” SEBAGAI LANGKAH PENANGGULANGAN DIABETES - Ahmad Zakiy Ramadhan (Graduate School of the Indonesia Institute of the Arts Yogyakarta, 2017)
People’s lifestyle today can be said to have been very bad, starting from diet, activity, until the rest, everything is not in its part. Meals ranging from mild to severe food straggle to various points across the country. Culinary business as though there is no ending, even continue to increase at it will. Advances in technology is growing rapidly, all competing to offer convenience in the activity. This development is inversely related to community health awareness. Low physical activity level, mixed with uncontrolled diet lead to the appear of degenerative diseases such as diabetes. Visual communication design is a study that is considered capable of being a problem solver. In designing a public service ad, it takes step by step to realize it. Starting from research on diabetes, target audience analysis until the realization process. The messages changing lifestyle of the people with visual media that expected to overcome the problem of diabetes in this country. Messages are metaphors that can be an alternative as the idea of creating public services advertisement.